MONEY CIRCULATION ON THE GREAT SILK ROAD - Ziyodakhon Turg‘unboyeva, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article provides information about the history and functioning of the ancient trade route known as the Great Silk Road, which operated from antiquity until the 14th century, and examines its influence on states and human life. In particular, certain considerations regarding monetary circulation along this trade route are presented. The article also discusses contemporary efforts aimed at reviving the Great Silk Road and the reasons underlying these initiatives.